A Study Of The Effect Of Human Soul On External Objects : Between Copenhagen School And Mulla Sadra - Ali Arshad Riahi (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
Abstract : The theory of the effects of all human souls on external objects, from the viewpoint of Copenhagen School (in Quantum Physics), has made physicists deny the existence of two separate realms of the observer and the observed; they claim that causality is meaningless and profess that it is impossible to recognize the object. While, on the other hand, Mulla Ṣadra believes that the effect of soul on external objects is limited to the souls of prophets as well as saints and, barring evil eye or supplications, there is no such effect in others. In this article we argue that, based on Mulla Ṣadra’s teachings and philosophical doctrine, it is actually possible to generalize this effect to other human souls. Consequently, it is impossible to have an accurate recognition of the causes of events if causality is considered meaningless. In addition, it is feasible to have cognition about these causes of events through gnostic intuition. Keywords : human soul, external objects, Copenhagen School, Mulla Ṣadra, unity, causality   Abstrak :  Teori tentang efek jiwa seluruh manusia terhadap objek-objek eksternal, dari sudut pandang Madzhab Copenhagen (dalam Fisika Kuantum), telah membuat para fisikawan mengingkari keterpisahan dua alam, yaitu subjek dan objek; berdasarkan keyakinan ini, mereka mengklaim bahwa [hukum] kausalitas menjadi gugur dan tidak berguna, dan mereka juga percaya bahwa mengetahui sepenuhnya objek adalah tidak mungkin. Sementara, di tempat lain, Mulla Ṣadra meyakini bahwa jiwa yang berefek terhadap objek-objek eksternal terbatas pada jiwa para nabi dan orang-orang suci. Ia juga meyakini bahwa tidak berefeknya jiwa-jiwa manusia biasa kecuali pada perbuatan-perbuatan seperti yang ia sebut sebagai ‘evil eye’ dan doa. Dalam artikel ini, kami berupaya membuktikan bahwa, berdasarkan ajaran dan doktrin filsafat Mulla Ṣadra, pengaruh (efek) jiwa manusia dapat digeneralisir. Dengan demikian tidak mungkin untuk mengetahui secara akurat sebab-sebab berbagai peristiwa dengan mengatakan bahwa hukum kausalitas adalah tidak berguna. Padahal, sebab-sebab segala sesuatu sangat mungkin diketahui melalui intuisi gnostis. Kata-kata kunci : jiwa manusia, objek-objek eksternal, Madzhab Kopenhagen, Mulla Ṣadra, penyatuan, hukum kausalitas.